Comparative Study on Trunk Range of Motion in Land Balance Tests and Snow Skiing: Implications for Para‐Alpine Sit‐Ski Performance: A Cross Sectional Study - Yusuke Ishige; Yuki Inaba; Noriko Hakamada; Akio Kobayashi; Shinsuke Yoshioka (Health Science Reports)
ABSTRACT Background and Aims In the present study, we examined the effect of trunk range of motion (ROM) on turn performance in Para Alpine Skiing by comparing the ROM of the trunk on land with that of the trunk on snow in different classes. We attempted to clarify the relationship between impairment tests and athletic performance by examining the relationship between centripetal acceleration during skiing and trunk ROM, which is difficult to reproduce during athletic activities on land. Methods Six male and four female skiers from sitting classes participated in this study. MRI images of the trunk and thigh were obtained. The ROM of the trunk was measured using the motion capture method during the Board Test on land and freeskiing on snow. Results The ROM of the trunk in the Board Test increased with a lower degree of disability. However, there was no relationship between the ROM of the trunk on snow and the degree of disability. A number of lateral flexion angles during turns exceeded the ROM of the trunk on land. The magnitude of centrifugal force did not depend on the degree of impairment. The relationship between the centrifugal force and the lateral flexion angle was linear. Conclusion The Board Test is an appropriate impairment test. During the turn, the body is passively moved because of the centrifugal force acting on it, a value that significantly exceeds the ROM of the trunk on land. The ROM of the trunk on snow was independent of the degree of disability.